Experience of Teaching Anthropology: Interrogating the Semester System at Tribhuvan University, Nepal - Dahal, K.B (University of Sri Jayawardenepura, 2021)
This article deals with the teaching of medical anthropology and research methodology under the newly reintroduced semester system at Tribhuvan University, Kathmandu, Nepal. It mainly consists of my experience of teaching anthropology under the semester-based education system in its Central Department of Anthropology for postgraduate anthropology students. In addition, it comprises of information acquired from students and colleagues from the Department and other colleges about the very subject. This paper does not provide any guideline for a better course of action for teaching anthropology. Instead, this paper emphasizes the imperativeness of the semester system that facilitates employing student-centred and interactive teaching and encourages elevating their potential through the effective teaching-learning mechanism. It portrays how the typical pedagogical approaches adopted under the semester system can contribute crucially to facilitate students to enhance their skills in critical reading and creative writing.